2023
DOI: 10.3390/molecules28237691
|View full text |Cite
|
Sign up to set email alerts
|

Illicium verum L. (Star Anise) Essential Oil: GC/MS Profile, Molecular Docking Study, In Silico ADME Profiling, Quorum Sensing, and Biofilm-Inhibiting Effect on Foodborne Bacteria

Emira Noumi,
Iqrar Ahmad,
Mohd Adnan
et al.

Abstract: Illicium verum, or star anise, has many uses ranging from culinary to religious. It has been used in the food industry since ancient times. The main purpose of this study was to determine the chemical composition, antibacterial, antibiofilm, and anti-quorum sensing activities of the essential oil (EO) obtained via hydro-distillation of the aerial parts of Illicium verum. Twenty-four components were identified representing 92.55% of the analyzed essential oil. (E)-anethole (83.68%), limonene (3.19%), and α-pine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Like the results obtained herein, Luís et al [73] demonstrated the ability of IVEO to inhibit quorum sensing, eradicate the already formed biofilm, and disperse pre-formed biofilms of A. baumanii. Another investigation also found IVEO to be effective in eradicating S. aureus biofilm-forming bacteria on polystyrene and glass surfaces [42]. In the same study, the authors discovered that IVEO exhibited a stronger inhibitory effect on the migration of Pseudomonas aeruginosa PAO1, with a 38% inhibition rate at a concentration of 100 µg/mL, when compared to its primary component, trans-anethole [42].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Like the results obtained herein, Luís et al [73] demonstrated the ability of IVEO to inhibit quorum sensing, eradicate the already formed biofilm, and disperse pre-formed biofilms of A. baumanii. Another investigation also found IVEO to be effective in eradicating S. aureus biofilm-forming bacteria on polystyrene and glass surfaces [42]. In the same study, the authors discovered that IVEO exhibited a stronger inhibitory effect on the migration of Pseudomonas aeruginosa PAO1, with a 38% inhibition rate at a concentration of 100 µg/mL, when compared to its primary component, trans-anethole [42].…”
Section: Discussionmentioning
confidence: 91%
“…Another investigation also found IVEO to be effective in eradicating S. aureus biofilm-forming bacteria on polystyrene and glass surfaces [42]. In the same study, the authors discovered that IVEO exhibited a stronger inhibitory effect on the migration of Pseudomonas aeruginosa PAO1, with a 38% inhibition rate at a concentration of 100 µg/mL, when compared to its primary component, trans-anethole [42].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Star anise (Illicium verum Hook. f.), as known globally, generates an annual output value exceeding 10 billion RMB [1] and is extensively utilized in both the food and pharmaceutical industries [2]. This spice is a common ingredient in the culinary traditions of China and Southeast Asia, enhancing the flavor of meat dishes [3], and it is also employed in Western countries for the production of sweet wines, confections, and cakes [4].…”
Section: Introductionmentioning
confidence: 99%
“…I. verum, as a globally significant research material, has been the subject of several literature reviews. However, these reviews often focus on food or medical aspects [2,23] and do not adequately reflect the dynamic evolution of research in this area.…”
Section: Introductionmentioning
confidence: 99%